Efektivitas dan Efisiensi Pengelolaan Pendapatan Asli Daerah untuk Menjamin Ketercukupan Kapasitas Fiskal Daerah Otonom Baru Kabupaten Mamuju Utara Provinsi Sulawesi Barat - Tope, Patta; Darman, Darman (Jurnal Aplikasi Manajemen, 2014)
This study aims to determine the effectiveness and efficiency of the local original income management, as well as an improved formulation of the local original income to ensure the adequacy and efficiency of local fiscal capacity in the new autonomous region in West Sulawesi. Based on these objectives, we used analysis of effectiveness and efficiency ratio source revenue targets by local governments and real potential. The results of the analysis indicate effectiveness ratio based on the target area of tax management effective while the analysis is based on the potential showed opposite results not effective. This suggests that the target of the government's tax revenue is small in area or not adapted to the existing potential. In addition, the local government budget spent compared to the amount of revenues classified as ery efficient. If connected with the analysis of the effectiveness of taxes and levies based on the potential that are not effective, then this indicates that the low budget/expenses incurred Northern Mamuju Government result in low tax revenues and levies.